Clinical applications of optical coherence tomography angiography: What we have learnt in the first 3 years. Issue 5 (September 2018) - Cohen, Salomon Y; Miere, Alexandra; Nghiem-Buffet, Sylvia; Fajnkuchen, Franck; Souied, Eric H; Mrejen, Sarah
A review of the literature from 2014 to 2016 was conducted, focusing on the results of optical coherence tomography angiography in different chorioretinal diseases. In only 3 years, optical coherence tomography angiography has been shown to be an effective tool for diagnosing choroidal neovascularization complicating age-related macular degeneration, pathologic myopia, and inflammatory conditions. The technique has sometimes been considered superior to conventional multimodal imaging, for example, in choroidal neovascularization associated with chronic central serous chorioretinopathy or multifocal choroiditis. In retinal vascular diseases, optical coherence tomography angiography has helped to understand the condition described as paracentral acute middle maculopathy and has been considered highly effective for the analysis of retinal vascular macular changes secondary to retinal vein occlusion or macular telangiectasia. Changes in the foveal avascular zone, also reported in diabetic maculopathy, have been shown to occur before any angiographic signs. A reduction in capillary vascular density has been reported in the fovea of eyes with malignant melanoma, but not in eyes with choroidal nevus. However, optical coherence tomography angiography is a recent technique that probably needs refinements and further studies. Nevertheless, the first 3 years of optical coherence tomography angiography use suggest its clinical relevance and useful applications in daily clinical practice.